Stubborn Poetries : Poetic Facticity and the Avant-Garde - Quartermain, Peter (Modern and contemporary poetics., 2013)
This is a study of poets whose work, because of its difficulty, apparent obduracy, or simple resistance to conventional explication, remains more-or-less firmly outside the canon. The focus of these essays is on nonmainstream poets - often unknown, unstudied, and neglected writers whose work bucks preconceived notions of what constitutes the avant-garde.